Production and Characterisation of Cell-Bound Lipases Secreted by a Newly Isolated Strain of Geotrichum Candidum - Mohd Ghazali, Hasanah (1990)
Indigenous lipolytic microorganisms were successfully isolated from soil samples collected from an oil palm plantation and were identified up to the generic level. Over seven hundred microbial colonies were screened and fifteen were found to be positive for the hydrolysis of triolein. Of these, three were yeast species, another three were strains of Geotrichum candidum and the rest were bacteria. Studies on the lipolysis of various natural oils on solid media and in liquid media by the yeasts and the G. candidum strains showed that the latter were the most potent lipolytic organisms. One of the yeasts was found to be weakly lipolytic. These organisms shared two common features: they were not able to hydrolyse tributyrin and they hydrolysed palm kernel olein, which is a lauric acid oil, poorly. Results obtained indicated that these organisms probably elaborated extracellular lipases that possessed some degree of fatty acid specifiCity. The cultural conditions for the maximal hydrolysis of palm olein and for the production of extracellular lipases, both soluble and cell-bound, in submerged culture were determined for one of the G. candidum strains. The optimal pH for lipolysis and maximal production of lipases occurred at pH 7.0 - 7.2. It was discovered that the soluble lipase of this organism was produced constitutively. The cell-bound lipase, however, was found to be an inducible enzyme where production took place only when an oil was added to the culture medium. The type of oil used did not affect production significantly but the presence of sugars and glycerol decreased lipase productivity markedly. High levels of glycerol suppressed growth of the organism. The cell-bound lipase was characterised and was shown to be most active at 43°C and preferred p-nitrophenylcaprylate as the substrate. The kinetics of the hydrolysis of various fatty acid esters of p-nitrophenolwere studied and the Km and Vmax values are presented. When the enzyme was stored at 4°C, a second temperature optimum developed at 30˚C. Continued storage resulted in an increase in the activity at 30˚C with a concomittant decrease in activity at 43˚C. After 6 days, the temperature optimum at 430C was completely lost The shift in temperature optimum from 43˚C to 30˚C could be quickly achieved by heating the ceU-bound lipase at 4O"C for 2 h. The extraction of the cell-bound lipase of G. candidum was simply and easily achieved by shaking induced cells in a buffer solution. Complete extraction could be accomplished in 4-5 h and the total enzyme activity recovered was 4.6-fold greater than what was initially measured and found to be bound to the ceUs. Magnesium ions when added to the extraction buffer caused a delay in the release of the enzyme from the cells. The most efficient pH for extraction was pH 8.4. The extracted lipase was most active at pH 7.8. This enzyme had two temperature optima : 33°C and 4O˚C. The temperature optimum at 33°C was observed only upon storage of the enzyme extract at 4°C. When in the soluble form, the cell-bound lipase preferred p-nitrophenylpalmitate as the substrate, instead of p-nitrophenylcaprylate. The Km and Vmax values of the enzyme for this ester was 6.7 mm and 6.3 x 10₃ umol/min, respectively. The rate of hydrolysis of olive oil exceeded the rate of hydrolysis of tributyrin by 4 times. The profiles of the hydrolysis of a number of fatty acid esters of p-nitrophenol, olive oil and tributyrin of the extracted lipase and those of several commercial lipases were obtained and compared. Purification of both the extracted lipase and soluble lipase was performed and the results obtained are presented. Gel filtration of cell-bound extract and soluble lipase extract on Sephadex G-150 revealed that the G. candidum produced at least two cellbound lipase and two soluble lipase isozymes. The molecular weights of the bound lipases were estimated to be 75,000 and 58,000-61,000, respectively.